1926
DOI: 10.1002/jmor.1050430103
|View full text |Cite
|
Sign up to set email alerts
|

The chromosomes of the house mouse

Abstract: AUTIIOR'S ABSTRACTThere are forty chromosomes in spermatogonia and twenty in primary sperniatocytrs. The sex chromosomes are of the usual X-Y type. Especial attention has been devoted to the study of chronioson~e morphology, both in spermatognnia and in primary sperniatocytes.The sprrrnatogenesis of the domestic mouse has been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1927
1927
1983
1983

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The majority of univalents occurring in both of our strains belonged to the small chromosome groups. This is not surprising since small chromosomes have fewer chiasmata (S l iz y n s k i, 1960) and have been observed to separate precociously (Cox, 1926). E d w a r d s (1970) found widely separated univalents belonging to the 21-22 group in an oocyte taken from a 35-year-old woman.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of univalents occurring in both of our strains belonged to the small chromosome groups. This is not surprising since small chromosomes have fewer chiasmata (S l iz y n s k i, 1960) and have been observed to separate precociously (Cox, 1926). E d w a r d s (1970) found widely separated univalents belonging to the 21-22 group in an oocyte taken from a 35-year-old woman.…”
Section: Discussionmentioning
confidence: 99%
“…Until 1969, geneticists and cytogeneticists believed that the karyotype of virtually all house mice (Mus musculus or Mus domesticus) consisted of 40 acrocentric chromosomes (Cox, 1926). Although animals with fewer than 40 chromosomes had now and then been found among laboratory mice (Evans, Lyon & Daglish, 1964;Leonard & DeKnudt, 1967;White & Tijo, 1967;Baranov & Dyban, 1971), they were regarded as rare exceptions.…”
Section: Introductionmentioning
confidence: 99%
“…The crucial studies of the second division have been carried out in insects and in various forms of plants. There are only a few workers such as WINIWARTER (1912,1919), WINIWARTER and OGUMA (1926), Cox (1926) Except NAKAMURA and MINOUCHI, however, none of these authors have shown the diad nature of the chromosomes in the metaphase of the second division. Generally the chromosomes in the metaphase of the second division resemble those of the anaphase of the first division in shape and structure, and those in the anaphase of the second those of the spermatogonium.…”
Section: Discussionmentioning
confidence: 99%